Vectors to Target Protein Domains to Different Cellular Compartments. (April 1998) - Toby, Garabet; Law, Susan F.; Golemis, Erica A.
The pcDNA3 mammalian expression vector uses the cytomegalovirus (CMV) promoter to express proteins cloned into an adjacent polylinker. We have modified this vector to create three different targeting constructs: Go to Plasma Membrane (pGTM), Go to Nucleus (pGTN) and Go to Nucleus, Activate Transcription (pGTNAT). pGTM expresses a protein as a fusion to a myristic acid attachment signal, which targets proteins to the cell membranes. pGTN expresses an inserted protein as a fusion to a nuclear localization sequence (NLS), targeting it to the nucleus. pGTNAT incorporates an NLS (directing proteins to the nuclear compartment), an acid blob (a transcriptional activation domain) and a hemagglutinin epitope tag, creating a 107-amino acid fusion domain. We then cloned green fluorescent protein (GFP) into the three novel vectors and pcDNA3, and we transfected HeLa cells to test the new targeting constructs. Immunofluorescence analysis showed that the GFP protein localizes to the nucleus when over-expressed in pGTN and pGTNAT, localizes to the plasma membrane and perinuclear membrane when in pGTM and is ubiquitous through the cell in pcDNA3. We anticipate that these new vectors will prove very useful in future expression studies to examine the function of particular proteins when they are localized to specific cellular compartments.